2015
DOI: 10.1039/c5ra13183a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of molecularly imprinted polymers based on magnetic carbon nanotubes for determination of sulfamethoxazole in food samples

Abstract: An efficient approach was developed to synthesize the imprinted magnetic carbon nanotubes nanocomposite and apply for sulfamethoxazole enrichment from milk and honey samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 52 publications
(46 reference statements)
2
22
0
Order By: Relevance
“…Molecularly imprinted polymers (MIPs) can selectively and efficiently recognize different target molecules due to their adjustable shape, size, and functional groups . Since their chemical robustness, physical and thermal stability, low preparation cost, reusability, and high specificity, MIPs are ideal adsorbents for SPE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecularly imprinted polymers (MIPs) can selectively and efficiently recognize different target molecules due to their adjustable shape, size, and functional groups . Since their chemical robustness, physical and thermal stability, low preparation cost, reusability, and high specificity, MIPs are ideal adsorbents for SPE.…”
Section: Introductionmentioning
confidence: 99%
“…their adjustable shape, size, and functional groups [14][15][16][17]. Since their chemical robustness, physical and thermal stability, low preparation cost, reusability, and high specificity, MIPs are ideal adsorbents for SPE.…”
mentioning
confidence: 99%
“…The analytes were eluted with methanol-acetic acid (9:1, v / v ), the eluate was reduced and the residue was reconstituted with acetonitrile (1 mL). In comparison with the respective NIP, MIP adsorption capacity for SMO was higher, with Q max values of 864.9 μg/g, while binding specificity study between SMO, SMZ, sulfadimethoxine, sulfamerazine and sulfameter showed MIP selectivity over SMO and the imprinting factors were 10 for SMO, 1.7 for SMZ, 1.9 for sulfadimethoxine, 2.3 for sulfamerazine and 1.5 for sulfameter [ 86 ].…”
Section: Mip Applications For the Extraction Of Antibiotics In Milmentioning
confidence: 99%
“…Surface imprinting technique, which introduces solid materials as supports for imprinting polymerization, was developed to improve the binding capacity and site accessibility of imprinted materials . Several nanomaterials have been used as solid supports, including silica nanoparticles , carbon nanotubes , nanofibers , and magnetic nanoparticles . Among these nanostructured materials, magnetic Fe 3 O 4 nanoparticles (Fe 3 O 4 NPs) have exhibited promising applications due to their magnetic susceptibility, good biocompatibility, and low toxicity .…”
Section: Introductionmentioning
confidence: 99%